Design of Quizzy Car Game in an Engineering Education - Deshpande, Archana; Jha, Aakash (Journal of Engineering Education Transformations, 2022)
In engineering education it is important that student develop skills to face challenges of Industry. Teachers find it difficult to make student interested in the subjects which affects learning. Traditional teaching makes student passively engaged with content and hence learning do not happen effectively. Active learning makes students engage to enhance the learning and to enjoy the process of learning itself. Introducing games in as a tool to learn makes students feel interested and in a fun way learning can be possible. This paper presents a study of use of “Quizzy car game to learn concepts in engineering instrumentation subject.